2002
DOI: 10.1046/j.1526-100x.2002.10104.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Assessment of Genetic Diversity among Differently‐Aged Populations ofSpartina alternif loraon Restored Versus Natural Wetlands

Abstract: We collected naturally recolonizing Spartina alterniflora (smooth cord grass) from each of three restored sites and one undisturbed reference site in southwestern Louisiana to assess the impact of wetland restoration on genetic diversity. We used amplified fragment length polymorphisms (AFLPs) to produce 94 polymorphic genetic markers, which were used to characterize genetic diversity as average heterozygosity Ͻ H Ͼ and the proportion of polymorphic loci Ͻ P Ͼ . Overall our findings indicate that restored popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 15 publications
(10 reference statements)
7
66
5
Order By: Relevance
“…But aside from valued fisheries or threatened species, there has been only scant research on the role of genetics in restoration success and this is mostly on plants. Travis et al (2002) found that Spartina alterniflora that naturally colonized restored marshes had levels of genetic diversity as high or higher than reference sites. However, when plants are collected elsewhere and brought to a site, genetic diversity is not always as desired as was the case for eelgrass (Williams 2001).…”
Section: Relevance To Restorationmentioning
confidence: 94%
“…But aside from valued fisheries or threatened species, there has been only scant research on the role of genetics in restoration success and this is mostly on plants. Travis et al (2002) found that Spartina alterniflora that naturally colonized restored marshes had levels of genetic diversity as high or higher than reference sites. However, when plants are collected elsewhere and brought to a site, genetic diversity is not always as desired as was the case for eelgrass (Williams 2001).…”
Section: Relevance To Restorationmentioning
confidence: 94%
“…Significant high-marsh changes may not have had time to take place along newly altered shorelines depending on the variable being measured. Based on salt marsh restoration studies, plant biomass (Broome et al 1986;Roman et al 2002), genetic diversity (Travis et al 2002), fish utilization (Roman et al 2002;Able et al 2004), and sediment salinities (Walters 2009) can change rapidly within newly planted marshes, while changes in sediment organic content (Craft et al 1999), nutrient cycling (Thompson et al 1995;Craft et al 1999), infauna (Sacco et al 1994;Levin et al 1996), and plant canopy (Zedler 1993) tend to require significant time if not decades. Ecological changes in Narragansett Bay salt marshes only were detected after two decades of urbanization (Wigand et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analyses. We extracted DNA from seagrass rhizomes using a standard CTAB (hexadecyltrimethyl-ammonium bromide)-based method (Saghai-Maroof et al 1984, Rogers & Bendich 1985, Doyle & Doyle 1987, as described in Travis et al (2002). Leaf tissue was omitted from the extractions in order to avoid contamination of seagrass DNA with that of epiphytic algae.…”
Section: Methodsmentioning
confidence: 99%